1991
DOI: 10.3109/01480549109017878
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Effects of Piperine and Piperonyl Butoxide on Hepatic Drug-Metabolizing Enzyme System in Rats

Abstract: An i.p. administration of rats with piperine (100 mg/kg) and piperonyl butoxide (400 mg/kg) produced a significant decrease in hepatic cytochrome P-450, and activities of benzphetamine N-demethylase, aminopyrine N-demethylase and aniline hydroxylase 1 hr after the treatment. Twenty-four hr later, these parameters along with cytochrome b5 and NADPH-cytochrome c reductase remained depressed only in piperine-treated rats. In contrast, piperonyl butoxide caused a significant induction of these parameters with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…mp 81 C) 30 Preparation of 5-(3,4-dimethoxy phenyl)-2E,4E-pentadienoic acid pyrrolidine amide (19). Compound 4b (2.0 g, 8.5 mmol) was condensed with pyrrolidine (0.9 mL) as per the procedure described for 8 to furnish a crystalline solid (2.25 g, 92%), mp 148 C (analysed for C 17 C 21 Preparation of 5-(3,4-dimethoxy phenyl)-2E,4E-pentadienoic acid n-butyl amide (20).…”
Section: Preparation Of 3-(34-dimethoxyphenyl)-2e-propenal (3b)mentioning
confidence: 99%
See 2 more Smart Citations
“…mp 81 C) 30 Preparation of 5-(3,4-dimethoxy phenyl)-2E,4E-pentadienoic acid pyrrolidine amide (19). Compound 4b (2.0 g, 8.5 mmol) was condensed with pyrrolidine (0.9 mL) as per the procedure described for 8 to furnish a crystalline solid (2.25 g, 92%), mp 148 C (analysed for C 17 C 21 Preparation of 5-(3,4-dimethoxy phenyl)-2E,4E-pentadienoic acid n-butyl amide (20).…”
Section: Preparation Of 3-(34-dimethoxyphenyl)-2e-propenal (3b)mentioning
confidence: 99%
“…18 The natural alkaloid consumed world-wide produces dierential inhibition of CYPs. 2,19 When compared to another MDP-containing insecticide synergist piperonyl butoxide, the latter produced a strong biphasic eect, an initial inhibition followed by induction. 19 Though piperine also induced the CYP1A1 activity by transcription activation, the overall inhibition of benzo(a)pyrene metabolism and AHH activity appeared to be the consequence of direct interaction of piperine with CYP1A1 gene product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies suggested that piperine nonspecifically inhibited many Cytochrome P 450 isoforms -CYP3A4 (main drug metabolizing microsomal enzyme) hepatic arylhydrocarbon hydroxylse, UDP-glucuronyltransferase and other enzymes involved in biotransformation of drugs and other xenobiotics (Atal et al, 1985;Singh et al, 1986;Bhardwaj et al, 2002). Moreover, piperine administration in rats resulted in 50% decrease of total Cytochrome P 450 content indicating a suicide inhibition by piperine (Dalvi, 1991). Thus, by inhibiting the microsomal enzyme system, piperine protects the drug from being metabolized/ oxidized in its first pass passage through the liver after being absorbed.…”
Section: Metabolic Conversionmentioning
confidence: 99%
“…Piperine is a pungent alkaloid present in black and white pepper (Piper nigrum), long used as a spice and preservative. [6] Piperine has been shown to alter both the bioavailability [7] and biotransformation [8,9] of xenobiotics, and to alter lipid peroxidation and availability of glutathione in the liver [10] and intestine. [11] Piperine has also been demonstrated in in vitro experiments…”
Section: Introductionmentioning
confidence: 99%